Roads, Labor Markets, and Human Capital : Evidence from Rural Indonesia - Yamauchi, Futoshi (World Bank Group, Washington, DC, 2015)
This paper uses household panel data from rural Indonesia to examine the impact of road quality on labor supply and wages. First, road projects are found to increase transportation speed. Second, the empirical results from intra-village variations of household endowments and labor market behavior show that an increase in transportation speed raised wages in nonagricultural and agricultural employment, and was associated with a decline in working time in agricultural employment, for households whose members are relatively educated. The findings support potential complementarity between road quality and education.